An economic and carbon analysis of biomethane production from food waste to be used as a transport fuel in Mexico. (20th September 2018) - Chan Gutiérrez, Enrique; Wall, David M.; O'Shea, Richard; Novelo, Roger Méndez; Gómez, Miguel Moreno; Murphy, Jerry D.
Abstract: Biomethane produced from food waste is a potential fuel for urban buses in Mexico to reduce greenhouse gas (GHG) emissions in transport. Biomethane from food waste can potentially produce 42.32 PJ per year, equivalent to 6.5% of the energy content of diesel used in transport in 2015. By replacing diesel with biomethane from food waste, a reduction of 17.91 MtCO2 e can be effected, 6.06% of the 2050 GHG emissions target. The economic feasibility of a biomethane plant for a Mexican city was investigated using two scenarios: co-digestion of food waste and sewage sludge (scenario 1); and co-digestion of food waste and pig slurry (scenario 2), both scenarios utilising anaerobic high density polyurethane digesters. Economic performance based on net present value (NPV) gave a positive outcome for scenario 1 with 33% of the revenue coming from gate fees. The levelised cost of energy (LCOE) for biomethane was $US 11.32/GJ ($US 40c/m 3 CH4 ). Scenario 2 has a negative NPV; to break even (LCOE) biomethane has to be sold at $US 14.38/GJ ($US 51 c/m 3 CH4 ). Biomethane from scenario 2 can be economically viable if a subsidy of $US 1.38/GJ is applied, equivalent to 5% of the cost of diesel. Highlights: 6.5% of diesel used in transport could be displaced by biomethane from food waste. Food waste biomethane achieves 6% of the greenhouse gas emissions reduction target. Co-digestion of food waste and sewage sludge to biomethane is financially feasible. A 60, 000 t/year co-digestion plant could fuel 136 urban buses per annum.